Toksisitas Akut Dermal Senyawa Mengkudu (Morinda citrifolia L.): Literature Review - Herman Widjaja; Aryanilo Aryanilo; Adylla Adawyah Haryana; Junaida Pramesti; Mario Parningotan Hutapea; Susana Jelita Lestari Tandang; Pida Khaerunisa; Raditha Dellafanny; Fulgencia Maria Amelia De Jesus Soares; Winda Novaliani (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Noni (Morinda citrifolia L.) is a medicinal plant widely used in traditional medicine due to its various pharmacological activities, such as anti-inflammatory, antibacterial, and antioxidant properties. However, the topical use of natural products requires safety evaluation to ensure they do not cause toxic effects on the skin. This article aims to review studies regarding the acute dermal toxicity of noni compounds and to assess their safety based on the toxicological parameters employed. A systematic literature review was conducted by searching scientific databases such as PubMed, Scopus, and Google Scholar. The findings indicate that noni extracts generally exhibit low dermal toxicity and do not cause mortality or significant clinical changes in test animals at specific dosages. However, some studies have reported instances of mild, transient irritation. Thus, noni shows potential for safe development as a topical preparation, although further research is required to confirm the safety of long-term use.